(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In the present decade, a rising alarm of ecological matters of emissions, especially worldwide warming and the boundaries of energy resources has resulted in wide-ranging research into novel technologies of producing electrical power. Thermoelectric power generators have appeared as a promising alternative green technology due to their distinct advantages. Thermoelectric power generation offer a prospective application in the direct conversion of waste-heat energy into electrical power where it is needless to think the cost of the thermal energy input. The submission of this alternative green technology in converting waste-heat energy directly into electrical power can also improve the overall efficiencies of energy conversion systems. In this article, the fundamental concepts and production of thermoelectric power by waste-heat energy i.e. an unconventional green skill are reviewed and discussed.